Renal evaluation in patients with type 2 diabetes mellitus and its association with diastolic blood pressure (Medical Journal of Indonesia, 2016)
Background: HbA1c is correlated with the estimated glomerular filtration rate (eGFR) and diastolic blood pressure (DBP). Our main objective was to evaluate the trend of biochemical and clinical variables, in relation to the eGFR in patients with type 2 diabetes mellitus (T2DM). Methods: This was a retrospective, longitudinal, and descriptive study, including patients with T2DM, who were cared for from January 2014 until December 2014, at the Clínica de Diabetes, Hospital Regional “Gral. Ignacio Zaragoza", ISSSTE, Mexico City, Mexico. eGFR was calculated using three formulas: the chronic kidney disease – epidemiology collaboration (CKD-EPI), Cockcroft-Gault, and modification of diet in renal disease (MDRD), during two periods of observation, 3 and 6 months. The results were compared by Student t tests or Wilcoxon-Mann-Whitney test depending on the variable distribution. Pearson correlation was employed to determine the relation between the eGFR determined with each formula and the analyzed variables. Results: The mean age was 56.5±11.3 years in the group of 3 months’ follow-up (n=110) and 57.1±13.8 years in the group of 6 months’ follow-up (n=47). In both groups, the formula with the lowest percentages of cases of CKD was CKD-EPI and the difference of this formula had a basal and final significant positive correlation with the DBP. Conclusion: The CKD-EPI formula showed the lowest percentages of cases of CKD in a short follow-up period, and its difference is consistently associated with the DBP, confirming the importance of controlling the later to mitigate the evolution to CKD.